Efektivitas Penerapan Metode Discovery Learning Dengan Tipe Numbered Heads Together (NHT) Untuk Meningkatkan Hasil Belajar PAI (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
This research is motivated by the fact that many students still get low PAI learning outcomes, this is because the methods used by teachers have not encouraged students' enthusiasm to learn well. The purpose of this study was to determine the effectiveness of the application of the Discovery Learning method with the Numbered Heads Together (NHT) type to improve the PAI learning outcomes of grade IV students at SDN 29 Dadok Tunggul Hitam. The type of research is a quasi-experimental design with an experimental design of a pre-test and post-test control group design. The population in the study was all grade IV students totaling 50 students with a research sample of class IV A totaling 25 students as the experimental class and class IV B totaling 25 students as the control class. The sampling technique was random sampling. This study used an objective question instrument. Data processing used parametric statistical tests paired sample t-test and independent sample t-test. The findings of the results in the study were (1). The average application of the Discovery Learning method with the NHT type was 3.43. This means that the application of the Discovery Learning method with the NHT type is good. (2). Student learning outcomes in the NHT type Discovery Learning method are high (91.12) while the conventional method with the expository type is sufficient (76.44). (3). The NHT type Discovery Learning method is effective in improving PAI learning outcomes. The effectiveness test obtained was 1.68 in the range of d > 0.8 in the high category. The conclusion of the study is that the NHT type Discovery Learning method is effective in improving PAI learning outcomes.
Keywords: Effectiveness; Discovery Learning; Numbered Heads Together; Learning Outcomes